2004
DOI: 10.1007/s10384-004-0096-5
|View full text |Cite
|
Sign up to set email alerts
|

Retinal Blood Flow in the Macular Area Before and After Scleral Buckling Procedures for Rhegmatogenous Retinal Detachment Without Macular Involvement

Abstract: The retinal microcirculation in the macular area was disturbed in RRD patients without macular involvement. It correlated with the extent of the RRD, and subsided 1 month after successful scleral buckling procedures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
39
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(40 citation statements)
references
References 11 publications
1
39
0
Order By: Relevance
“…It has been reported that the retinal microcirculation in the macular area was impaired in patients even without macular involvement and it recovered in 1 month after successful scleral buckling procedures. 6 This study has several weaknesses that limit the generalization of the findings. There were only a small number of patients studied, the follow-up times were different, and there was a lack of the findings of other tests (e.g., angiography, electrophysiology, and visual fields) that support the choroidal circulation disturbances.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…It has been reported that the retinal microcirculation in the macular area was impaired in patients even without macular involvement and it recovered in 1 month after successful scleral buckling procedures. 6 This study has several weaknesses that limit the generalization of the findings. There were only a small number of patients studied, the follow-up times were different, and there was a lack of the findings of other tests (e.g., angiography, electrophysiology, and visual fields) that support the choroidal circulation disturbances.…”
Section: Discussionmentioning
confidence: 88%
“…The decrease in circulation recovered to normal within 1 month after the buckling surgery. 6 However, several cases have been reported on progressive visual field defects (VFDs) after retinal reattachment surgery using encircling buckling for peripheral RRD. 7 In these cases, the ocular blood flow, especially the tissue blood flow in the neuroretinal rim of the optic disk, was significantly lower than that of the unaffected fellow eye.…”
Section: Introductionmentioning
confidence: 99%
“…Nagahara et al 13 , using laser speckle flowgraphy, reported no marked change in the normalised blur value, which is an index of tissue blood velocity, in the choroid and retina of the foveal region in patients with retinal detachment without macular involvement. In contrast, Eshita et al, 14 using scanning laser Doppler flowmetry, reported that the retinal circulation in the macular region was disrupted in these patients. Although the POBF is thought to reflect the total pulsatile choroidal blood flow (ChBF), 15 laser Doppler flowmetry can evaluate choroidal circulation in the foveal region.…”
mentioning
confidence: 81%
“…A reversible reduction in retinal tissue blood flow has been reported in the macula of eyes with macula-on RRD using scanning laser Doppler flowmetry. 51 A previous LSFG study of eyes with macula-on RRD found that ONH tissue MBR was not significantly lower in eyes with focal RRD than in healthy fellow eyes. 52 Although it is still very difficult to form postoperative visual prognoses for eyes with macula-off RRD, recent advancements in OCT measurements of circular foveal volume have allowed us to make quantitative predictions.…”
Section: Monitoring Ocular Circulationmentioning
confidence: 97%